Anaerobna kapaciteta pri cestnih kolesarjih mlajših kategorij - Rauter, Samo (Šport (Ljubljana), 2018)
Endurance is the major contributing factor to succeeding in cycling. Another important parameter is power which is essential in race finishes, accelerating during the races and riding uphill. Anaerobic capacity test is used to determine and monitor these motor abilities. In this research 30 s Wingate test was used to measure anaerobic capacity. Measurements were carried out in December 2017 and January 2018 on 43 cyclists in junior age categories of the Slovenian Cycling Federation. They were divided into three age categories (9 cyclist age 15-16, 22 cyclist age 17-18 and 15 cyclist age 19-23). Results of anaerobic test confirmed different absolute and relative power values in these age groups. Criteria were established in these groups for future cyclists to determine which of them could become winners of the age group. Interpretation of all measurements acquired in years will be able in the following years as we gather even more information. This data will be of great value to the cyclists, coaches and head coaches of the Slovenian Cycling Federation.
Keywords: anaerobna kapaciteta; antropometrija; kolesarji; mladi kolesarji; Wingate test